Analisis Perbandingan Penggunaan Mutu Baja Pada Bangunan Gedung Rumah Sakit Condong Catur Bedasarkan SNI 2847-2019 - Monica Novi Anggreini,; Zulaicha, Lilis (ReTII, 2023)
Concrete and reinforcing steel are the main materials for building reinforced concrete structures. Reinforcing steel with different steel grades has a major influence in planning a construction. Comparative analysis of the quality of steel is needed to find out what differences arise from its use. By comparing the variations in the quality of fy steel: 380 MPa, 400 MPa, 420 MPa, and 440 MPa with the SAP2000 application, SP Column and Microsoft Exel, it will be known that the resulting differences are different. The results of this analysis will provide a comparison of the effectiveness of its use, so that it can reduce errors in selecting the quality of reinforcing steel used in construction and will create buildings that are safe, comfortable, sturdy, and economical. Keywords: Reinforced Concrete, Reinforcing Steel, Steel Quality, Comparison, Analysis